2015
DOI: 10.2463/mrms.2014-0073
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Evaluation of Trunk Muscle Recruitment after Trunk Exercises using Diffusion-weighted MR Imaging

Abstract: Purpose: We evaluated trunk muscle recruitment in abdominal and back exercises with magnetic resonance (MR) diffusion-weighted imaging.Methods: Twelve men performed bent-knee sit-up, crunch, trunk lateral flexion, and trunk extension exercises. We obtained axial diffusion-weighted images of the trunk before and after each exercise using a 1.5-tesla MR system, calculated apparent diffusion coefficient (ADC) values from the right and left rectus abdominis, lateral abdominal, psoas major, quadratus lumborum, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The bundles of the muscles can be clearly demonstrated using diffusion tensor tractography. Change of apparent diffusion coefficient has been observed even in the Trunk muscles between before and after training 16) . Change of diffusion tensor parameters after long-distance running (marathon) also has been reported 17) .…”
Section: Dti Outside the Brainmentioning
confidence: 93%
“…The bundles of the muscles can be clearly demonstrated using diffusion tensor tractography. Change of apparent diffusion coefficient has been observed even in the Trunk muscles between before and after training 16) . Change of diffusion tensor parameters after long-distance running (marathon) also has been reported 17) .…”
Section: Dti Outside the Brainmentioning
confidence: 93%
“…There were no significant age-related differences. osmotic pressure due to metabolite accumulation in the extravascular space, or a combination of these factors, which can increase extravascular water within an exercised muscle (9). In a previous study, Katzberg et al (10) reported that the severity of disc displacement without reduction was greater than that of disc displacement with reduction.…”
Section: Tablementioning
confidence: 99%
“…In a previous study, the apparent diffusion coefficient (ADC) values on MRI of the masticatory muscles on the painful and non-painful sides were compared in 106 TMD patients with unilateral pain, and the mean ADC values of the muscles on the painful side were significantly greater than those on the non-painful sides (p < 0.01) [31]. Yanagisawa et al [32] reported that an increase in ADC value on the painful side was indicative of edematous changes and indicated an increase in intramuscular water transport, including water diffusion in the extravascular space and microcirculation in the capillary network. In our study, it is thought that the lower FF value on the disc displacement side reflects a relative decrease in fat content due to increased water content resulting from edematous changes caused by pain.…”
Section: Plos Onementioning
confidence: 99%